2019
DOI: 10.30870/jels.v4i2.6100
|View full text |Cite
|
Sign up to set email alerts
|

Discussion and Think-Pair-Share Strategies on the Enhancement of EFL Students’ Speaking Skill: Does Critical Thinking Matter?

Abstract: Previous research has underscored the importance of learning strategies and critical thinking. However, the relationship between both constructs toward the enhancement of the students' speaking skills in EFL context still receives scant attention. Therefore, this study aims to investigate the influence of learning strategies (i.e. Discussion Strategy and Think-Pair-Share Strategy/TPS) mediated by critical thinking on the speaking skill of the Department of English Education students at a private university in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Students learn not only by memorizing the material, but students learn by exchanging information with their friends. This statement is supported by the results of research [6] with the title "The influence of the think pair share type of cooperative learning model on the mathematics learning outcomes of class VIII students of SMPN 17 Bengkulu City" which results in that the think pair share type of cooperative learning is more effective than other types of cooperative learning.…”
Section: Introductionmentioning
confidence: 59%
“…Students learn not only by memorizing the material, but students learn by exchanging information with their friends. This statement is supported by the results of research [6] with the title "The influence of the think pair share type of cooperative learning model on the mathematics learning outcomes of class VIII students of SMPN 17 Bengkulu City" which results in that the think pair share type of cooperative learning is more effective than other types of cooperative learning.…”
Section: Introductionmentioning
confidence: 59%
“…Also, the real-life experiences (TS-3) has built students' critical thinking (CT) and encouraged them (Almalki, 2019;King et al, 2010) to see and evaluate different phenomena from various point of views (De Bono, 1982;Nikijuluw & Puspitasari, 2018;Sharma & Priyamvada, 2017;Sharma et al, 2020). In addition, with regard to Teachers' Strategies-12 (TS-12), students were provided with guidance in implementing higher order thinking (HOT) skills by providing logical arguments and reasons (Brookhart & Bronowicz;2010;Tuzlukova et al, 2017;Warliati et al, 2019) to support their opinions and presenting relevant evidence to support the answers (Obs-ET1, ET2 & ET3).…”
Section: Teachers' Strategies To Promote Students' Critical Speaking ...mentioning
confidence: 99%
“…They emphasized the importance of teaching methods in influencing this process. Similarly,Warliati, et al (2019) studied the relationship between learning strategies, critical thinking, and speaking skills. Warliati's research showed that the Discussion Strategy was more effective than the Think-Pair-Share Strategy in promoting these skills.…”
mentioning
confidence: 99%